A review on the diagnosis, natural history, and treatment of familial hypercholesterolaemia. - Marks, D; Thorogood, M; Neil, H; Humphries, SE (2003)
BACKGROUND: Familial hypercholesterolaemia (FH) affects approximately 1 in 500 people (10 million world-wide) and the elevated serum cholesterol concentrations lead to a more than 50% risk of fatal or non-fatal coronary heart disease by age 50 years in men and at least 30% in women aged 60 years. Based on a systematic literature search, we review the natural history of FH, describe the diagnostic criteria, and consider the effectiveness of treatment. METHODS: A comprehensive review was conducted of the literature on the diagnosis of FH, the morbidity and mortality related to treated and untreated FH, and the evidence on the effectiveness of treatment of FH in adults and children. Treatment options have changed since statin treatment became available, and we have not considered pre-statin therapy studies of treatment effectiveness. FINDINGS AND DISCUSSION: A clinical diagnosis of FH is widely used, but a definitive diagnosis can be made by genetic screening, although mutations are currently only detected in 30-50% of patients with a clinical diagnosis. Under-diagnosis of FH has been reported world-wide ranging from less than 1% to 44%. The relative risk of death of FH patients not treated with statins is between three and fourfold but treatment is effective, and delays or prevents the onset of coronary heart disease. Early detection and treatment is important. Aggressive LDL therapy is more effective in the regression of the carotid intima media thickness than conventional LDL therapy. Diagnosis at birth is problematic, and should be delayed until at least 2 years of age. Statins are not generally recommended for the treatment of children up to adolescence. Resins may be used but poor adherence is a problem. Technical advances in mutation detection, and the identification of other genes that cause FH, are likely to have important implications for the cost effectiveness of genetic diagnosis of FH.